2017
DOI: 10.4209/aaqr.2016.07.0297
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of PM2.5 Particles: Influence of Outdoor Particles on Indoor Environment of Schools Using Chemical Mass Balance

Abstract: Children have higher lung function than adults and they spend most of their day time in schools. Also, children studying at schools located in the vicinity of busy roadways are vulnerable to childhood asthma and respiratory disorders. The present study is focused on estimating the sources of PM 2.5 particles present in the indoor air quality in schools which are located adjacent to urban and suburban roadways. The indoor PM 2.5 samples from all the four schools were collected using fine dust sampler from 8 a.m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Transported pollutants at any site may also increase the load of contaminants, and the source-apportionment studies are found to be useful for finding the regions, which are responsible for transported pollution to any location (e.g. [25,40]). This situation, however, may be different at coastal stations during the winter season, where land-sea breeze interacts with the atmospheric boundary layer variation, and pollutants concentrations are changing during diurnal cycle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Transported pollutants at any site may also increase the load of contaminants, and the source-apportionment studies are found to be useful for finding the regions, which are responsible for transported pollution to any location (e.g. [25,40]). This situation, however, may be different at coastal stations during the winter season, where land-sea breeze interacts with the atmospheric boundary layer variation, and pollutants concentrations are changing during diurnal cycle (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Jenis kegiatan mempengaruhi kadar PM 2,5 di wilayah tersebut. 8 Pemantauan konsentrasi Black Carbon dan PM 2,5 di beberapa kota besar di Indonesia dari bulan Januari-Desember 2011 didapatkan rata-rata konsentrasi PM 2,5 dan black carbon untuk area Bandung (PM 2,5 : 18,35µg/m 3 ) dan Jakarta (PM 2,5 : 16,50 µg/m 3 ) lebih tinggi dibandingkan dengan Yogyakarta (PM 2,5 : 8.78 µg/m 3 ). Kondisi ini menunjukkan polusi yang terjadi di Bandung dan Jakarta lebih tinggi daripada di Yogyakarta.…”
Section: Pendahuluanunclassified
“…Moreover, most of the indoor PM 2.5 studies mainly focused on the indoor levels of PM 2.5 , source apportionment, and the indoor-outdoor relationship [17,18,19,28,29,30]. There has been little research on the spatial and temporal distributions of indoor PM 2.5 concentrations.…”
Section: Introductionmentioning
confidence: 99%